Why school is important: It's more than education. Issue 5 (10th April 2019) - Knopf, Alison
Abstract : Most parents know that school is an important part of their children's education. But new research has shown that it's also a part of good health. About 13% of students across the United States miss 15 or more days of school a year. Chronic absenteeism makes children more at risk for poor long‐term health outcomes, according to research published in Pediatrics, the journal of the American Academy of Pediatrics.